2017
DOI: 10.1093/jac/dkw550
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring and use of an adjusted body weight strategy for high-dose voriconazole therapy

Abstract: A high-dose voriconazole regimen produced initial supratherapeutic troughs that required dose adjustment downward by nearly 30%. Adjusted body weight dosing in obese patients resulted in a similar maintenance dose to total body weight dosing in the non-obese, and appears to be a sensible dosing strategy for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…However, an actual body weight-adjusted dosing regimen may not be feasible for obese patients, as this would lead to high VRC concentrations (Davies-Vorbrodt et al, 2013;Koselke et al, 2012). A dosing regimen based on adjusted body weight has been proposed (Davies-Vorbrodt et al, 2013;Koselke et al, 2012;Richards et al, 2017), and further studies are needed. In the current study, no obese patient (body mass index !30 kg/m 2 ) was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, an actual body weight-adjusted dosing regimen may not be feasible for obese patients, as this would lead to high VRC concentrations (Davies-Vorbrodt et al, 2013;Koselke et al, 2012). A dosing regimen based on adjusted body weight has been proposed (Davies-Vorbrodt et al, 2013;Koselke et al, 2012;Richards et al, 2017), and further studies are needed. In the current study, no obese patient (body mass index !30 kg/m 2 ) was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dosing based simply on the actual WT may not be feasible, especially for obese patients. An adjusted WT dosing strategy has been proposed but needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Initial supratherapeutic levels have been obtained in obese patients (BMI .35 kg/m 2 ) with 12 mg/kg, whereas maintenance doses (8.5 mg/kg) were similar to those in nonobese patients. 139 Intravenous VRZ doses should be based on ABW or IBW (rather than TBW) and careful TDM should be implemented. 138 Dose adjustment to lean body weight (LBW) has been proposed for FCZ, but not VRZ a priori, but caution is required in the use of ABW (possible risk of higher levels of exposure in poor CYP2C19 metabolizers).…”
Section: Coexisting Factors Obesity Bariatric Surgerymentioning
confidence: 99%